Sistem Informasi Keuangan PT. Damai Alam Sejahtera Lobu Siregar Kecamatan Siborong-Borong Berbasis Web - Nababan, Margaretta; Purba, Eviyanti Novita; Lumbantoruan, Gortap (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Currently, there are still many corporate agencies that do not use computerized systems, the same goes for PT. Damai Alam Sejahtera Lobu Siregar, Siborong-borong District. Financial System at PT. The existing Peace of Alam Sejahtera Lobu Sigerar is no longer in accordance with current developments, so it is still not well structured. Especially for financial systems, in this system what is processed is income, expenditure and report data. Systems can be defined in two groups of approaches, the first system approach places more emphasis on procedures, the second system approach places more emphasis on elements or components. The problem currently occurring is the slow processing of data, the reports produced must go through unstructured data collection. In the information system to fulfill this task, we will explain how to design a web-based financial information system. In designing this system, Entity Relational Diagrams and Data Flow Diagrams are used, while data collection uses observation, interviews, and literature studies. This website was created using the PHP programming language and MySQL as the database. It is hoped that this application system will further help Admin performance in PT finance. Peace Alam Sejahtera Lobu Siregar has become more effective and efficient.